Prominent hardware post Latarjet mimicking shoulder instability symptoms - Yeak, Raymond Dieu Kiat; Mohd Nasir, Mohd Nizlan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
A 29-year-old man, who was a medical intern presented with history of recurrent shoulder dislocation. Radiographs and computed tomography imaging revealed a bony bankart lesion with glenoid bone loss of 25% with moderate Hill- Sachs lesion. Latarjet surgery was performed. At post-operative 8 months, the patient experienced pain and clicking in the left shoulder while performing cardiopulmonary resuscitation. At post-operative 1 year, magnetic resonance arthrography showed a united coracoid graft and intact posterior labrum. Left shoulder diagnostic arthrosco-py and removal of Latarjet screws through a limited anterior deltopectoral approach were performed. The symptoms pain, clicking and instability sense was caused by either the prominent distal screw or the remnant suture material from the anchor which resulted in impingement of the infraspinatus muscle. We recommend the use of image intensifier to check on the position and length of the screw at the end of the surgery to avoid this complication.